Renal Denervation and Renal Stenting are Beginning to Show Benefits in Hypertension and Other Conditions - Lederman, Lynne (MD Conference Express, 2013)
Renal denervation is a new therapeutic intervention being studied for the treatment of resistant hypertension (HTN). The procedure has other potential applications in which it could be studied since other disease processes are characterized by increased sympathetic activity. Other renal interventions such as stenting may also relieve HTN and improve renal function, although the benefits have yet to be demonstrated. This article discusses sympathetic modulation in cardiovascular disease, including renal denervation for HTN and other potential applications, as well as multiple clinical trials.